Unsettling difference : music drama, the Bible, and the critique of German Jewish identity - Nester, Adi, 1984- (Cornell University Press and Cornell University Library, 2024)
"Unsettling Difference examines the discourse of German Jewish difference and identity as it is expressed in biblical-themed operas, their German-language literary sources, and the aesthetic and intellectual debates that surrounded their creation in the first half of the twentieth century."-- Provided by publisher.
"A Signale Book" - from titlepage.
Keywords: Bible -- Influence.; Jews -- Germany -- Identity -- History -- 20th century.; Jews -- Germany -- Civilization -- History -- 20th century.; Juifs -- Allemagne -- Identité -- Histoire -- 20e siècle.; Juifs -- Allemagne -- Civilisation -- Histoire -- 20e siècle.